Exploring the Dynamics of Environmental DNA: Effects of Early Developmental Stage and Physiological State in Chum Salmon - Masayuki K. Sakata; Takashi Kanbe; Shunpei Sato; Hitoshi Araki (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) analyses provide valuable ecological data. Recent studies have explored eDNA dynamics related to reproductive behavior and developmental stages, revealing significant variations in eDNA concentrations across different life stages. However, there is a gap in understanding the association between eDNA concentrations and changes before and after developmental events, such as egg hatching. This study addresses this gap by monitoring eDNA signals in chum salmon (Oncorhynchus keta) during their early developmental stages and examining the effects of their physiological and behavioral changes. For this purpose, eDNA flux was monitored in rearing experiments with chum salmon during their developmental stages (egg, alevin, and fry). The eDNA flux varied significantly across different developmental stages: while no eDNA was detected during the egg stage, eDNA flux increased rapidly after hatching. After hatching, the eDNA flux became stable during the alevin stage but increased approximately 30‐fold when they progressed into the fry stage (LMM and post hoc Tukey‐HSD test: p < 0.05). These results suggest that eDNA signals vary across the developmental stages and can be utilized to estimate and monitor fish development even under natural conditions, such as those occurring under gravel for salmonid species.